2017
DOI: 10.1007/s00381-017-3414-1
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cranial fossa tumours in children at National Cancer Institute, Sudan: a single institution experience

Abstract: Overall, this study draws attention to the situation of paediatric brain tumours in Sudan. Late presentation, misdiagnosis and limited diagnostic and treatment resources are challenges that may contribute to poor outcome in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…For meta‐analyses, all studies reporting ARs were assembled and narrowed to one study per institution, leaving the same 38 studies representing 2497 children in 14 countries. We found only one report of AR from a low‐income country (Sudan) . When reports were pooled by country, ARs ranged from < 5% in several countries (Brazil, Iran, Jordan, El Salvador, Venezuela, and Egypt) to 42% in Pakistan (Table ).…”
Section: Overall Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For meta‐analyses, all studies reporting ARs were assembled and narrowed to one study per institution, leaving the same 38 studies representing 2497 children in 14 countries. We found only one report of AR from a low‐income country (Sudan) . When reports were pooled by country, ARs ranged from < 5% in several countries (Brazil, Iran, Jordan, El Salvador, Venezuela, and Egypt) to 42% in Pakistan (Table ).…”
Section: Overall Resultsmentioning
confidence: 94%
“…No studies attempted to formally analyze predictors of treatment abandonment in CNS tumors. However, authors of 12 studies reported possible causes of abandonment (Table ), based on their personal experience with patients, patient records, and knowledge of patients’ backgrounds . Only one (Chinese) study conducted a questionnaire with caregivers to identify reasons for abandonment .…”
Section: Overall Resultsmentioning
confidence: 99%
“…The incidence of CNS tumours is reduced in LMICs, which may reflect ethnic variation or limited neurosurgical resources or attenuated availability of advanced imaging equipment, such as CT and MRI scanners. 8,19 In the current study, the steep increase in the relative frequency of CNS tumours reported in the second and third periods (2006-2010 and 2011-2015) compared to the first period (1999)(2000)(2001)(2002)(2003)(2004)(2005) is likely because of the introduction of CT scan, MRI and neurosurgical services in central Sudan. …”
Section: Discussionmentioning
confidence: 94%
“…17 In Sudan, the main sources of data on childhood cancers are found in hospital-based case series. 12,13,18,19 Among all patients admitted to the NCI for treatment during the study period, children with cancers constituted 7.5%. This finding is similar to those of a previous study in Sudan, in which childhood cancers constituted approximately 7% of all cancer cases registered in the state of Khartoum from 2009 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number and type of cases diagnosed and referred will reflect local conditions in the primary health care system of a given country. 29 For example, in many LIC and L-MIC, the diagnosis of brain tumors is delayed due to lack of imaging, although this is slowly improving over time. 30 In general terms, patients can be divided into patients with a long life expectancy requiring potentially curative radiotherapy, and patients who require palliative radiotherapy for symptom control.…”
Section: Pediatric Cancers Commonly Referred For Radiotherapy In Lmicmentioning
confidence: 99%